Por uma vivência planetária eco-lógica: diálogos interfilosóficos em torno de uma ética da responsabilidade - Braga, Isaque Trevisam (2015)
At the present juncture of reality, where the unbridled path of the evolution and technological progress is echoed in the eagerness of human expectations regarding the search for unlimited access to the resources of nature and for a utopia of a scientific knowledge that arranges for the continual maintenance of its purposes, directing humanity to the danger of its own extinction, this research aims to promote, within its limitations, the diffusion of critical reflection on the technical and scientific development, the proper regulation of the means of production and the attempt for a practice of sustainable consumption, buoyed by the foundations of a deep ecology. Appropriating, respectively, of the inquiries and postures defended by Hans Jonas, Michel Serres and Fritjof Capra, methodologically it is proposed to approach the authors to systematize common keywords which turns to the divulgation of conceptual positions to be problematized and possible postures to be adopted under the observed circumstances. Therefore, it is concluded that, from an ecological perception of reality, it s imperative that mankind be elected as responsible for their own future and instructs itself by a acquaintanceship symbiosis with the environment, in connection with all strands of the web of life